Experiences of informal caregivers supporting individuals with upper gastrointestinal cancers: a systematic review - Melinda Furtado; Dawn Davis; Jenny M. Groarke; Lisa Graham-Wisener (BMC, 2024)
Abstract Background Upper gastrointestinal cancers (UGICs) are increasingly prevalent. With a poor prognosis and significant longer-term effects, UGICs present significant adjustment challenges for individuals with cancer and their informal caregivers. However, the supportive care needs of these informal caregivers are largely unknown. This systematic review of qualitative studies synthesises and critically evaluates the current evidence base on the experience of informal caregivers of individuals with UGIC. Methods A Joanna Briggs Institute systematic review was conducted. Searches were performed in four databases (MEDLINE, PsycINFO, Embase, CINAHL) from database inception to February 2021. Included studies explored experiences of informal caregivers of individuals diagnosed with primary cancer of the oesophagus, stomach, pancreas, bile duct, gallbladder, or liver. Studies were independently screened for eligibility and included studies were appraised for quality by two reviewers. Data were extracted and synthesised using meta-aggregation. Results 19 papers were included in this review, and 328 findings were extracted. These were aggregated into 16 categories across three findings: (1) UGIC caregiver burden; UGIC caregivers undertake extensive responsibilities, especially around patient diet as digestion is severely impacted by UGICs. (2) Mediators of caregiver burden; The nature of UGICs, characterised by disruptive life changes for caregivers, was identified as a mediator for caregiver burden. (3) Consequences of caregiver burden: UGIC caregivers' experiences were shaped by unmet needs, a lack of information and a general decline in social interaction. Conclusions The findings of this review suggest the need for a cultural shift within health services. Caregiving for UGIC patients is suggested to adversely affect caregivers' quality of life, similarly to other cancer caregiving populations and therefore they should be better incorporated as co-clients in care-planning and execution by including them in discussions about the patient's diagnosis, treatment options, and potential side effects.